Human Resource Development Indicators for the Iranian Judo Federation - Mohammadali Noudehi; Morteza Dousti; Seyed Mohammad Hossein Razavi; Masomeh Kalateh Seifari (The Society of Aging and Physical Activity (SAPA), 2017)
Objectives. The aim of this study was to identify and prioritize human resource development indicators for the Iranian Judo Federation. Methods. The present study was a combined (mixed) research. The research population consisted of officials from the Federation, the national team coaches and members, delegation officials, university professors, and other experts (n=96). The sampling was purposeful and based on availability. The data were collected by both- interviews and a researcher-designed questionnaire. Its content validity was confirmed by 10 professors who worked in the field of sports management. The reliability of the questionnaire was obtained using Cronbach's coefficient alpha (α=0.79). Results. The four factors (in order of priority) for the development of human resources were as follows: motivation, training and promotion, performance evaluation, and absorption of the human resources. Conclusion. According to the results, motivation is the most important factor for the development of human resources and the Judo Federation authorities need to focus attention on motivational strategies to enhance performance and develop their country's human resources in this particular sport.